P483The DNA glycosylase Neil3 improves survival in myocardial infarction by regulating fibroblast proliferation and function. (15th July 2014) - Olsen, MB; Hildestrand, GA; Vinge, LE; Alfsnes, K; Sjaastad, I; Christensen, G; Yndestad, A; Aukrust, P; Bjoraas, M; Finsen, AV
Abstract: Accumulation of DNA damage due to impaired base excision repair (BER) may play a role in the pathogenesis of myocardial failure. The DNA glycosylase Neil3 is known to carry out BER during oxidative stress induced DNA damage, but is also thought to have a role in stem cell biology. Based on this, we hypothesized that Neil3 plays a role in myocardial remodeling during heart failure (HF). qPCR showed an increased expression of Neil3 in myocardial biopsies from patients with severe HF, and that the Neil3 expression significantly decreased following improvement of myocardial function following treatment with left ventricular assist device. In a murine model of myocardial infarction (MI) we found a strong upregulation of Neil3 on day 3, 7 and 21 after MI. At day 7, myocardial cell isolation revealed a low Neil3 expression in cardiomyocytes, while a 2.5- and a 4.5-fold increased expression was found in endothelial cells and fibroblasts, respectively, following MI compared to sham. In leukocytes an equally high expression of Neil3 was observed in both sham and MI. Using Neil3 knock-out (KO) mice we found a significantly higher mortality in KO compared to wild type (WT) mice after MI ( 73% vs. 40%), despite smaller infarct sizes in the Neil3 KO, as determined by MRI. The first week post MI, all animals died from cardiac rupture. Zymography on protein extracts from the infarcted tissue revealed significantly increased levels of MMP2 in the Neil3 KO, 3 days after MI. Immunohistochemistry (IHC), at the same time point, showed similar numbers of inflammatory cells measured by the presence of Ly6G+ neutrophils, Mac2+ monocytes/macrophages and CD45+ leukocytes. At day 6 a significantly higher number of Ki67+ proliferating cells were observed in the Neil3 KO infarcted areas. In accordance with this, primary cardiac fibroblasts lacking Neil3 showed a higher proliferation rate, measured both by BrdU and scrape wound assay. Furthermore, we found a significantly higher mRNA expression of both the myofibroblast marker α-SMA, and collagen type III in cardiac fibroblasts isolated from Neil3 KO mice 7 days post MI, indicating increased levels of activated fibroblasts and altered fibroblast function. IHC 6 days post MI showed the same tendency towards more α-SMA-positive fibroblasts and more collagen by Sirius red in the Neil3 KO infarcts, however these differences were not statistically significant. In conclusion, our data suggest that after MI, Neil3 plays a role in regulating fibroblast proliferation and function, affecting wound healing and extracellular matrix composition and quality, altogether reducing mortality.